2023
DOI: 10.1038/s41598-023-32891-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel oxidative-stress related lncRNA signature predicts the prognosis of clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is a primary malignant tumour of tubular epithelial origin and is most common in the urinary tract. Growing evidence suggests that oxidative stress (OS), generates high levels of reactive oxygen species (ROS) and free radicals, and plays a critical role in cancer in humans. However, the predictive value of OS-related long non-coding RNAs (lncRNAs) in ccRCC remains unclear. We constructed a predictive signature of survival based on OS-related lncRNAs that were obtained fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…One of these six signature-related lncRNAs, LINC00944 , was first reported by Chen et al ( 26 ) and was found to be elevated in RCC tissues and cell lines, and significantly correlated with tumor stage and prognosis in RCC ( 26 , 27 ). Additionally, LINC00944 was linked to immune microenvironment, ferroptosis, and oxidative stress, and it may be used to predict the prognosis of several cancers, including KIRC ( 26 - 30 ).…”
Section: Discussionmentioning
confidence: 97%
“…One of these six signature-related lncRNAs, LINC00944 , was first reported by Chen et al ( 26 ) and was found to be elevated in RCC tissues and cell lines, and significantly correlated with tumor stage and prognosis in RCC ( 26 , 27 ). Additionally, LINC00944 was linked to immune microenvironment, ferroptosis, and oxidative stress, and it may be used to predict the prognosis of several cancers, including KIRC ( 26 - 30 ).…”
Section: Discussionmentioning
confidence: 97%
“…Multivariate Cox regression analysis was used to identify DE-MRGs that provided a prognostic signature. ROC and KM analysis were used to evaluate the prognostic value of the signature 52 , 53 . The GSE37745 dataset was used to validate the prognostic signatures.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, activating transcription factor 3 (ATF3 were correlated with RCC progression [28], genes ABCB1, AGER, E2F1, FOXM1, HADH ISG15, KCNMA1, PLG, and TEK were correlated with the clinical outcome and immune status of ccRCC patients [27], genes UCN, PLG, FOXM1, and HRH2 were associated with the ccRCC prognosis [29], long non-coding RNAs (lncRNA) SPART-AS1, AL162586.1 Based on bioinformatic analysis, several current studies have identified sets of genes related to oxidative stress (ORG). For instance, activating transcription factor 3 (ATF3) were correlated with RCC progression [28], genes ABCB1, AGER, E2F1, FOXM1, HADH, ISG15, KCNMA1, PLG, and TEK were correlated with the clinical outcome and immune status of ccRCC patients [27], genes UCN, PLG, FOXM1, and HRH2 were associated with the ccRCC prognosis [29], long non-coding RNAs (lncRNA) SPART-AS1, AL162586.1, LINC00944, LINC01550, HOXB-AS4, LINC02027, and DOCK9-DT were associated with ccRCC aggressiveness [30,31], mitochondrial genes ACAD11, ACADSB, BID, PYCR1, SLC25A27, and STAR were linked to the ccRCC prognosis [12], and genes ADAM8, CGN, EIF4EBP1, FOXM1, G6PC, HAMP, HTR2C, ITIH4, LTB4R, MMP3, PLG, PRKCG, SAA1, and VWF, and microRNAs related to the redox status and ccRCC progression [12], were found to be essential for the response to oxidative stress. Recently, a transcription factor for the oxidative stress response, broad complex-tramtrack-bric-a-brac and cap 'n' collar homology 1 (BACH1), has been labeled an essential factor involved in RCC progression in vivo [32].…”
Section: Cellular Stress In Rcc Biologymentioning
confidence: 99%
“…It is known that the constitutive upregulation of growth factors (vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), insulin-like growth factor 2 (IGF2), erythropoietin) and the induction of hypoxiainducible factor 1α (HIFα) contribute to RCC development by stimulating vascularization and aberrant cell proliferation and inhibiting apoptosis [36]. Additionally, branched-chain keto-acid dehydrogenase kinase upregulation in ccRCC, extracellular vesicles, exosomes, cancer stem cell reactivation, long non-coding RNA (lncRNA), microRNA (miRNA), and mRNA enable communication between cells in the TME, indirectly or directly contributing to tumor development, angiogenesis, invasion, and RCC metastasis [2,30,37,38]. Branchedchain keto-acid dehydrogenase kinase is the rate-limiting enzyme of branched-chain amino acid metabolism, upregulated in ccRCC [38].…”
Section: Cellular Stress In Rcc Biologymentioning
confidence: 99%